Inhaltskontrolle von Arbeitsverträgen - Singer, Reinhard (Schriftenreihe der Juristischen Gesellschaft zu Berlin ;, 2007)
Before the reform of law of contract the law on protection from inequitable standard business conditions was not applicable to contracts of employment. One objective of the modernization of contract law was to raise the protective level of employment law to the level of general civil law. Contracts of employment are now subject to a check of the contents in terms of the law on standard business conditions. However, suitable account must be taken of the special features that apply in employment law when the provisions governing standard business conditions are applied to contracts of employment.